Letters and Epistolary Culture in Early Medieval China - Richter, Antje (Book collections on Project MUSE., 2013)
This book of personal letters and letter-writing in premodern China focuses on the earliest period (ca. 3rd-6th cent. CE) with a sizeable body of surviving correspondence. Along with the translation and analysis of many representative letters, the author explores the material culture of letter writing (writing supports and utensils, envelopes and seals, the transportation of finished letters) and letter-writing conventions (vocabulary, textual patterns, topicality, creativity).